Complete mitochondrial genome of the Antarctic fur seal (Arctocephalus gazella). Issue 2 (3rd July 2019) - Nagel, Rebecca; Forcada, Jaume; Hoffman, Joseph I.
Abstract: The Antarctic fur seal ( Arctocephalus gazella ) is an abundant Antarctic otariid. Here, we present the complete mitochondrial DNA sequence of this species, which includes 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and the control region for a total length of 16, 156 bp. A phylogenetic analysis including all 25 publically available pinniped mitogenomes nested the Antarctic fur seal within the Otariid clade, which was clearly resolved from the Phocidae and Odobenidae.